Keragaman Plankton di Sungai - Nurhasanah Ritonga; Arman Harahap (BIOEDUSAINS: Jurnal Pendidikan Biologi dan Sains, 2022)
This study aims to determine plankton diversity in the Aek Pala River, Labuhanbatu Regency. The method used is descriptive observative. Sampling was done by filtering 10 L of water using a plankton net. The results showed that there were 15 genera of plankton in Aek Pala waters, including 10 types of phytoplankton and 5 types of zooplankton. The most abundant diversity of phytoplankton species found was in the class Chlorophyceae, which was 75% (7 species). In contrast, the highest diversity of zooplankton species is from the class Crustacea (3 species). In addition, the physical and chemical parameters of the waters show that Aek Pala waters are very good for supporting plankton life. In conclusion, the diversity of plankton species obtained included phytoplankton (classes Chlorophyceae, Bacillariophyceae and Dinophyceae) and zooplankton (classes Crustacea and Rotifera). The abundance of plankton found categorizes that the river waters have moderate fertility. Keywords: Diversity, Plankton, Zooplankton, Phytoplankton and Aek Pala River